Ungkapan Pantang Larang Wanita Hamil di Kenagarian Pangian Kecamatan Lintau Buo Tanah Datar - Yeni, Linda Fitri; Nurizzati, Nurizzati; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2013)
The purpose of this study were to describe the structure and meaning contained in the â€œngkapan pantang larangâ€ pregnant women who are at Kenagarian pangian District Lintau Buo Tanah Datar. This research isa qualitative study using descriptive methods. The data in this study is the â€œungkapan pantang larangâ€ pregnant women who are at Kenagarian pangian District Lintau Buo Tanah Datar. The findings of this study are: (1) structure of the â€œungkapan pantang larangâ€ pregnant women who are at Kenagarian pangian District Lintau Buo Tanah Datar, (2) the meaning of the â€œungkapan pantang larangâ€ pregnant women who are at Kenagarian pangian District Lintau Buo Tanah Datar.